A new strategy and its effect on adherence to intermittent preventive treatment of malaria in pregnancy in Uganda - Mbonye, Anthony K.; Yanow, Stephanie; Birungi, Josephine; Magnussen, Pascal (BioMed Central, 2013)
Background: Few women in Uganda access intermittent preventive treatment of malaria in pregnancy (IPTp) with sulfadoxine-pyrimethamine (SP). Previous studies have shown that high costs, frequent stock-out of drugs, supplies and poor quality of care are the greatest hindrance for women to access health services. In order to increase adherence to IPTp, we conceptualised an intervention that offset delivery care costs through providing a mama kit, created awareness on health benefits of IPTp and built trust between the provider and the client. Methods: The new strategy was conceived along four constructs namely: 1) creating awareness by training midwives to explain the benefits of SP and the importance of adhering to the two doses of SP as IPTp to all pregnant women who attended ANC and consented to the study. Midwives were trained for two days in customer care and to provide a friendly environment. The pregnant women were also informed of the benefits of attending ANC and delivering at health facilities. 2) Each woman was promised a mama kit during ANC; 3) trust was built by showing the mama kit to each woman and branding it with her name; 4) keeping the promise by providing the mama kit when women came to deliver. The strategy to increase adherence to two doses of SP and encourage women to deliver at health facilities was implemented at two health facilities in Mukono district (Kawolo hospital and Mukono health centre IV). The inclusion criteria were women who: i) consented to the study and ii) were in the second trimester of pregnancy. All pregnant women in the second trimester (4-6 months gestation) who attended ANC and consented to participate in the study were informed of the benefits of SP, the importance of delivering at health facilities, were advised to attend the scheduled visits, promised a mama kit and ensured the kit was available at delivery. The primary outcome was the proportion of pregnant women adhering to a two dose SP regimen. Results: A total of 2,276 women received the first dose of SP and 1,656 (72.8%) came back for the second dose. 1,069 women were involved in the evaluation (384 had participated in the intervention while 685 had not). The main reasons that enabled those who participated in the intervention to adhere to the two doses of IPTp and deliver at the study facilities were: an explanation provided on the benefits of IPTp and delivering at health facilities (25.1%), availability of a mama kit at delivery (24.6%), kind midwives (19.8%) and fearing complications of pregnancy (8.5%). Overall, 78.0% of these women reported that they were influenced to adhere to IPTp by the intervention. In a multivariable regression, nearby facility, P = 0. 007, promising a mama kit, P = 0.002, kind midwives, P = 0.0001 and husbands’ encouragement, P = 0.0001 were the significant factors influencing adherence to IPTp with SP. Conclusion: The new strategy was a good incentive for women to attend scheduled ANC visits, adhere to IPTp and deliver at the study facilities. Policy implications include the urgent need for developing a motivation package based on the Health-Trust Model to increase access and adherence to IPTp.
Keywords: Malaria in pregnancy; IPTp; Adherence; Mama kit; Health-Trust Model; Uganda